2022
DOI: 10.3390/su14053087
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Flood Risk Perception: A Case Study from Canada

Abstract: In recent years, understanding and improving the perception of flood risk has become an important aspect of flood risk management and flood risk reduction policies. The aim of this study was to explore perceptions of flood risk in the Petite Nation River watershed, located in southern Quebec, Canada. A survey was conducted with 130 residents living on a floodplain in this river watershed, which had been affected by floods in the spring of 2017. Participants were asked about different aspects related to flood r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…This higher perception of control was also associated with the feeling of being judged and a higher place identity, as well as age and the number of evacuations experienced. Previous studies have found that the experience of residents is a determinant of perceived risk, providing a better understanding and knowledge of risk [49]. It has also been associated with the intention to prepare [25].…”
Section: Discussionmentioning
confidence: 99%
“…This higher perception of control was also associated with the feeling of being judged and a higher place identity, as well as age and the number of evacuations experienced. Previous studies have found that the experience of residents is a determinant of perceived risk, providing a better understanding and knowledge of risk [49]. It has also been associated with the intention to prepare [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a limited number of tools available to evaluate society's perception of flash flood risk, and the present study aims to fill this gap by providing a new tool specifically tailored to evaluate the perception of flash flood risk in Iran (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous typologies of behavior that people can adopt in anticipation of a flood have been proposed (e.g., Dillenardt et al, 2022; Noll et al, 2022; van Valkengoed et al, 2022). One of these typologies, which distinguishes between structural measures (i.e., what is done on a house or land, such as waterproofing foundations) and nonstructural measures (i.e., what does not affect the house itself, such as drawing up an inventory of personal property) was used in several studies (e.g., Mondal et al, 2021; Noll et al, 2022; Oubennaceur et al, 2022; Valois et al, 2019; Valois, Bouchard, Talbot, et al, 2020). However, few studies have assessed if and how households and individuals adopt and implement structural adaptation measures and behaviors while also aiming to identify the key psychosocial determinants of their adoption (Babcicky & Seebauer, 2019; Grothmann & Reusswig, 2006; Valois et al, 2019; Valois, Tessier, Bouchard, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%